2013
DOI: 10.1134/s1027451013050273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the high-power ion-beam irradiation of a hydroxyapatite target on the properties of formed calcium phosphate coatings

Abstract: The physical-mechanical of properties of biocompatible calcium phosphate coatings deposited onto titanium and silicon substrates from erosion materials, which are generated by irradiating hydroxyapatite (synthetic and natural) targets by means of the high-power pulsed ion beam of a Temp-4 accelerator, are investigated. A calculation technique for predicting the rate and energy efficiency of deposition using pulsed ion beams is proposed. Their characteristics are analyzed as applied to the formation of calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is shown that K ev has a maximum capacity while the current density and energy density of the beam is increasing as well as its value increases with the increasing of the initial energy of beam particles. The calculations showed that the productivity and energy efficiency increase of the technology is possible when beams are generated with a prevailing content of protons and the energy density at the level of 5..10 J/cm 2 [7].…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that K ev has a maximum capacity while the current density and energy density of the beam is increasing as well as its value increases with the increasing of the initial energy of beam particles. The calculations showed that the productivity and energy efficiency increase of the technology is possible when beams are generated with a prevailing content of protons and the energy density at the level of 5..10 J/cm 2 [7].…”
Section: Methodsmentioning
confidence: 99%